Modulating functional and dysfunctional mentalizing by transcranial magnetic stimulation - Schuwerk, Tobias; Langguth, Berthold; Sommer, Monika (Frontiers in Psychology, 2014)
Mentalizing, the ability to attribute mental states to others and oneself, is a cognitive function with high relevance for social interactions. Recent neuroscientific research has increasingly contributed to attempts to decompose this complex social cognitive function into constituting neurocognitive building blocks. Additionally, clinical research that focuses on social cognition to find links between impaired social functioning and neurophysiological deviations has accumulated evidence that mentalizing is affected in most psychiatric disorders. Recently, both lines of research have started to employ transcranial magnetic stimulation: the first to modulate mentalizing in order to specify its neurocognitive components, the latter to treat impaired mentalizing in clinical conditions. This review integrates findings of these two different approaches to draw a more detailed picture of the neurocognitive basis of mentalizing and its deviations in psychiatric disorders. Moreover, we evaluate the effectiveness of hitherto employed stimulation techniques and protocols, paradigms and outcome measures. Based on this overview we highlight new directions for future research on the neurocognitive basis of functional and dysfunctional social cognition.